Four new species of pholcine spiders (Araneae: Pholcidae) from Southeast Asia - Yao, Zhiyuan; Li, Shuqiang; Jäger, Peter (Zootaxa, 2014)
Four new species belonging to four genera of the subfamily Pholcinae are reported from Southeast Asia: Belisana protumida spec. nov. (male, female), Khorata bayeri spec. nov. (male), Pholcus schawalleri spec. nov. (male), and Uthina khaosokensis spec. nov. (male).